PENGARUH MOBILISASI DINI TERHADAP PENYEMBUHAN LUKA POST OPERASI SECTIO CAESAREA DI RUANG NIFAS RS BHAYANGKARA MANADO - Yannerith Chintya; Ariska Ariska; Erika S.P. Marenda (JURNAL ILMIAH KESEHATAN MANADO, 2024)
Early mobilization management is one of the factors that influences post-operative wound healing and can reduce the risk of complications. Early mobilization is a policy to guide sufferers as quickly as possible to get out of bed and walk. Early mobilization can speed up the wound healing process because early mobilization can train the muscles for the wound healing process. The aim of the research is to determine the effect of early mobilization on post-caesarean section wound healing in the Postpartum Room at Bhayangkara Hospital, Manado.This research is quantitative using the type of research design used is "Quasi experimental posttest only with control group design". The research was carried out in February 2024 in the Postpartum Room at Bhayangkara Hospital, Manado. The population in this study was 34 respondents, the sample was 34 people who were divided into 2 groups, namely 17 respondents in the intervention group and 17 respondents in the control group. The statistical test used was the paried t-test with a significance level of 95% (α < 0.05).The results obtained showed that of the 17 respondents in the intervention group, most of them experienced good wound healing, namely 13 respondents (76.5%) and 17 respondents in the control group, most of them experienced good wound healing, namely 6 respondents (35,3%). The results of statistical tests using the paired t-test show that the p value is 0.003 or smaller than the α value of 0.05. It can be concluded that there is a difference in wound healing after caesarean section surgery in the intervention group which was given early mobilization compared to wound healing after caesarean section surgery in the control group which was not given early mobilization, meaning that there is an influence of early mobilization on post caesarean section surgery wound healing in the post-operative ward at Bhayangkara Hospital. Manado. The conclusion from the research results is that there is an effect of early mobilization on post-caesarean section wound healing in the Postpartum Room at Bhayangkara Hospital, Manado. Suggestions for health workers, including midwives, nurses, doctors, to be able to teach mobilization according to the SOP to post-caesarean section mothers for a better and faster post-caesarean section wound healing process.